Solid Solution Strengthening of Mo, Re, Ta and W in Ni during High-Temperature Creep - Lukas Haußmann; Hamad ur Rehman; Dorothea Matschkal; Mathias Göken; Steffen Neumeier (Metals, 2021)
Solid solution strengthening of the unordered γ matrix phase by alloying elements is of great importance during creep of Ni-based superalloys, particularly at high temperatures above 1000 °C. To study the role of different potent solutes, we have conducted creep experiments on binary Ni-2X alloys (X = Mo, Re, Ta, W) at 1000 °C, 1050 °C, and 1100 °C at a constant stress of 20 MPa. Compared to mechanical tests below 800 °C, where the size of the elements mostly determines the solid solution hardening contribution, the strengthening contribution of the different alloying elements above 1000 °C directly correlates with their diffusivity. Therefore, elements such as Ta that lead to strong solid solution hardening at low temperatures become less effective at higher temperatures and are exceeded by slower diffusing elements, such as Re.